A Study of Mechanical and Thermal Properties Polymer Blend from Polystyrene with Poly(Ô‘-Caprolactone) that Obtained Using Bis(Dibenzoylmethanato)Zirconium(IV) Chloride Catalyst - Yusuf, Muhammad; Utama, Erwinsyah (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Polystyrene (PS) is one form of the plastic that is most widely utilized for household application. However, plastics made from PS can pollute the environment. Hence, it is necessary to modify PS by mixing it with a biodegradable polymer like poly (É›-caprolactone) (PCL). The focus of this research was to determine the mechanical and thermal properties of PS/PCL polyblends. In this research, polyblend are prepared by mixing PS with PCL that acquired using the bis(dibenzoylmethanato)zirconium(IV) chloride bis(dibzm)2Zr catalyst. The method employed is solvent casting with a ratio of PS/PCL of 10/0, 10/1, 10/2, 10/3, and 10/4 (w/w). The optimum mechanical properties were obtained in 10/2 mixing which had a tensile strength of 6.72 MPa with 1.01% in elongation. Furthermore, the optimum PS/PCL polyblend was also characterized using DSC to determine its thermal properties.